Digital Replantations: Comparison Veins Anastomoses first versus Arteries Anastomoses first - Acciaro, Andrea Leti; Colzani, Giulia; Della Rosa, Norman; Starnoni, Marta; Adani, Roberto (Handchirurgie · Mikrochirurgie · Plastische Chirurgie, 2021)
Purpose This retrospective study analyses the effect performing veins anastomoses before arteries anastomoses in digital replantation.Patients and methods 38 adult patients with replantation of 12 thumbs and 39 fingers, in whom the veins anastomoses were performed prior to the arteries anastomoses, were compared with 29 patients with replantation of 9 thumbs and 30 fingers, in whom the arteries anastomoses were done first, with respect to the survival rate, total active motion, grip strength, and duration of the replantation.Results There was no significant difference between the two groups with respect to the survival rates, total active motion, and grip strength, while the duration of the replantation was significantly shorter in patients, in whom the veins anastomoses were performed prior to the arteries anastomoses (2 hours and 50 minutes versus 3 hours and 42 minutes; p < 0.001).Conclusion Performing veins anastomoses before arteries anastomoses in digital replantations reduces the replantation time significantly without influencing the survival rate and the clinical outcome.
Keywords: Digital replantation; venous anastomosis; arterial anastomosis; replantation time